2018
DOI: 10.3390/s18093077
|View full text |Cite
|
Sign up to set email alerts
|

HEAR: Approach for Heartbeat Monitoring with Body Movement Compensation by IR-UWB Radar

Abstract: Further applications of impulse radio ultra-wideband radar in mobile health are hindered by the difficulty in extracting such vital signals as heartbeats from moving targets. Although the empirical mode decomposition based method is applied in recovering waveforms of heartbeats and estimating heart rates, the instantaneous heart rate is not achievable. This paper proposes a Heartbeat Estimation And Recovery (HEAR) approach to expand the application to mobile scenarios and extract instantaneous heartbeats. Firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…First the signal was decomposed by EMD into Intrinsic Mode Functions (IMFs) to preserve any local property in the time domain, and then the Hilbert transform was used for finding the instantaneous frequency when the subject is nonstationary. Yin et al [80] have proposed a new algorithm for body movement compensation by IR-UWB radar. The results were verified by Bland-Altman analysis with a mean deviation smaller than 0.1 s. Large body movements were estimated by adopting a distance estimation method using a Kalman Filter and the k-Nearest Neighbor technique.…”
Section: Vital Signs Of a Non-stationary Subjectmentioning
confidence: 99%
“…First the signal was decomposed by EMD into Intrinsic Mode Functions (IMFs) to preserve any local property in the time domain, and then the Hilbert transform was used for finding the instantaneous frequency when the subject is nonstationary. Yin et al [80] have proposed a new algorithm for body movement compensation by IR-UWB radar. The results were verified by Bland-Altman analysis with a mean deviation smaller than 0.1 s. Large body movements were estimated by adopting a distance estimation method using a Kalman Filter and the k-Nearest Neighbor technique.…”
Section: Vital Signs Of a Non-stationary Subjectmentioning
confidence: 99%
“…reported the possibility of detecting myocardial motion using UWB radar during breath-holding 10 , many researchers have introduced various measurement methods and data processing algorithms for noncontact vital sign monitoring using UWB radar. Recent studies have shown the possibilities of measuring the heart rate (HR) using radar in subjects during respiration 11,12 , in moving subjects 13 and in subjects behind a wall 14 . Shi et al .…”
Section: Introductionmentioning
confidence: 99%
“…If the patient gets into accident and is helpless, emergency doctors will need to have access to the implanted devices by themselves, without assistance of the attending physician, bypassing the existing safety protocol. In such case using special vibration signal is proposed (Sun, Lo, & Lo, 2019;Yin et al, 2018;Yin et al, 2019).…”
Section: Methodsmentioning
confidence: 99%